22 SPHINGOSINE-1-PHOSPHATE-MEDIATED ENDOTHELIAL CELL MOTILITY IS REGULATED BY S1P1 RECEPTOR, LIPID PHOSPHATE PHOSPHATASE-1, AND SPHINGOSINE KINASE 1. (1st March 2006) - Gorshkova, I.; Berdyshev, E.; Saatian, B.; Zhao, Y.; Pendyala, S.; Garcia, J. G.N.; Natarajan, V.
Abstract : The extracellular effects of S1P, a naturally occurring and platelet-derived bioactive lipid molecule, are mediated by S1P1-5 family of G protein-coupled receptors. The exact role of different S1P receptors and signaling pathways regulating S1P-induced cell motility is not completely defined. Human pulmonary artery endothelial cells (HPAEC) expressed S1P1, S1P3, and S1P4 receptors with a predominance of S1P1, as determined by RT PCR. Exposure of HPAEC to S1P resulted in a potent induction of cell motility as determined by a scratch wound healing assay and by monitoring changes in transendothelial electrical resistance of wounded HPAEC by ECIS. Inverse agonist of S1P1 receptor, SB649146, and S1P1 siRNA attenuated S1P-induced EC motility. Furthermore, overexpression of sphingosine kinase 1 wild type and S1P1 wild type increased intracellular content of S1P as well DHS1P (DHS1P > S1P) with a concomitant loss of cell motility in response to exogenous S1P. Overexpression of lipid phosphate phosphatase (LPP)1 wild type that enhanced hydrolysis of exogenous S1P blocked S1P-induced cell motility. These results suggest that a balance between S1P1 expression and intracellular content of S1P and DHS1P seems to be critical for maintaining cellular sensitivity to external S1P stimulation. Supported by NIH RO1s HL 79396 and 71152 to V.N.